(1262) Comparative advantages in foreign trade المزايا النسبية في التجارة الخارجية - Grote, Gerhard (The Institute Of National Planning., 2018)
The world economy, since the early fifties, has been characterized, among other things, by an increasing role of the international division of Labour. Resulting from the growing internationalization of the economic life growth rates of foreign trade in most countries have exceeded by far the growth rates of industrial and agricultural production as well as of the national income.